Analysis of the efficiency of state, private and foreign banks of Ukraine - Rodionova, Tatyana; Piatkov, Artem (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
In the early 1990s, private capital began to play a significant role in Ukraine's banking system, while the public sector was represented by only two banks: Oschadbank and Ukreximbank. However, after the financial crisis of 2008-2009, the number of state-owned banks increased. As of the end of 2019, there were 75 banks in Ukraine (4 of them - state and 35 - with foreign capital). The subject of the study is the financial performance of public, private and foreign banks in Ukraine. The purpose of this article is to analyze and compare the efficiency of public, private and foreign banks in Ukraine for the period 2014-2019. To achieve the goal of the study, a quantitative approach to the study is used, using analysis of financial ratios such as net interest margin (NIM), average return on equity (ROAE), average return on assets (ROAA) and cost-to-income ratio (CIR). 4 state, 4 largest foreign and 2 private banks (by number of assets) were selected for the study. The study showed that the largest share of net assets in the banking system of Ukraine is occupied by state-owned banks, while the share of foreign banks continued to decline, and the share of private banks was the smallest in the banking system. However, the best indicators of net interest margin (NIM), average return on equity (ROAE), average return on assets (ROAA) and cost-to-income ratio (CIR) in the last 3 years were demonstrated by foreign banks. It should be noted that state-owned banks were able to significantly improve their results compared to 2016 (in particular, this applies to PrivatBank). To increase their efficiency, state-owned banks must get rid of non-performing loans (currently more than 63% of their loan portfolio is considered inefficient (UAH 403 billion)). Also, inviting foreign investors to the capital of state-owned banks can improve the performance of banks and provide significant additional revenues to the budget (from 15 to 40 billion UAH), which can significantly affect their revenue side.